Severe hyoglycemic attacks and remission of type 2 diabetes and psoriasis due to acitretin - Shukurov, Samir; Erkoç, Reha; İlhan, Mahmut Muzaffer; Özdemir, Mustafa; Alay, Murat; Taşan, Ertuğrul (Modestum Ltd, 2016)
An 59 year old women with type two diabetes and psoriasis admitted with severe hypoglycemic attacks. Acitretin use was identified as the cause of this attacks. Two years after cessation of acitretin, she is still in remission of diabetes and psoriasis. This condition was attributed to extraordinary prolonged use of acitretin.

59 yaşında tip iki diyabet ve psöriazis hastalığı olan kadın hasta ağır hipoglisemik ataklar ile başvurdu. Bu atakların nedeninin Asitretin kullanımı olduğu saptandı. Asitretinin kesilmesinin üzerine iki yıl geçmesine rağmen hastanın hem diyabet hem de psöriazis hastalıkları remisyondadır. Bu durumun Asitretinin sıra dışı olarak uzun süreli kullanımına bağlı olduğu düşünüldü.
Asitretine bağlı şiddetli hipoglisemik ataklar ve tip 2 diyabetes mellitusta ve psöriaziste remisyon
WOS: 000382752700012
Keywords: Acitretin; Hypoglycemia; Type 2 Diabetes Mellitus; Psoriasis; Asitretin; Hipoglisemi; Tip 2 Diabetes Mellitus; Psöryazis